Implementation of the SIPINTER Licensing Policy at the Investment and One-Stop Integrated Licensing Agency of Tangerang Regency - Fafa Nurcahyo; Edy Sutrisno (Politeia : Journal of Public Administration and Political Science and International Relations, 2026)
This research examines the suboptimal implementation of the Integrated Licensing Service Information System (SIPINTER) at the Investment and One-Stop Integrated Licensing Agency of Tangerang Regency as an e-Government instrument for achieving effective, transparent, and accountable governance. The study aims to analyze the factors causing the ineffectiveness of SIPINTER and formulate strategies for its optimization. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The analysis is based on Indrajit’s (2002) e-Government framework, support, capacity, and value. The findings show that although SIPINTER has contributed to bureaucratic modernization and improved service quality, its implementation remains ineffective. Key obstacles include low digital literacy, limited technical competence of government personnel, unstable system and server infrastructure, and weak cross-agency coordination. These issues reduce licensing compliance and limit SIPINTER’s contribution to local revenue (PAD). To address these challenges, the study proposes three strategic steps: (1) strengthening public outreach and digital literacy; (2) enhancing digital work culture through visionary leadership and smart government–based training; and (3) developing technological infrastructure and optimizing regional and national funding for digital transformation. Analytical tools were used to ensure robust strategy formulation. SWOT analysis identified internal and external factors influencing SIPINTER, followed by the TOWS matrix to develop strategic alternatives. These strategies were then evaluated and prioritized using Multi-Criteria Analysis (MCA) based on feasibility, effectiveness, resource needs, and expected impact. The integration of SWOT–TOWS–MCA ensured that the recommended strategies are theoretically sound and operationally applicable for improving SIPINTER’s implementation.